ChemInform Abstract: Reactive Metal‐Oxide Interfaces: A Microscopic View. Issue 16 (March 2016) - Picone, A.; Riva, M.; Brambilla, A.; Calloni, A.; Bussetti, G.; Finazzi, M.; Ciccacci, F.; Duo, L.
Abstract: Review: latest achievements in the understanding of metal/oxide and oxide/metal layeresystems; 294 refs.